Prospective REALITI-A StudyTake-home Points - Cristiano Caruso, MD, PhD; G. Walter Canonica, MD; Manish Patel, MBChB, PhD; Andrew Smith, MBChB, PhD; Mark C. Liu, MD; Rafael Alfonso-Cristancho, MD, PhD; Robert G. Price, MSc; Rupert W. Jakes, PhD; Lydia Demetriou, MSc; Antonio Valero, MD; Thomas C. Köhler, MD; Charles Pilette, MD, PhD; et al. (CHEST Pulmonary)
Background: Mepolizumab, a monoclonal antibody targeting IL-5, is of proven clinical benefit in severe asthma; however, prospective, long-term, real-world data in severe asthma are required. Research Question: What is the real-world benefit of 2 years of mepolizumab treatment in severe asthma? Study Design and Methods: REALITI-A was a 2-year, international, prospective study enrolling adults with asthma on newly initiated mepolizumab 100 mg subcutaneously (physician decision). Outcomes in the 1-year premepolizumab vs 2-year follow-up periods included rates of clinically significant asthma exacerbations (CSEs) (deterioration requiring systemic corticosteroids and/or emergency department [ED] visit/hospitalization), exacerbations requiring ED visit/hospitalization, exacerbations requiring hospitalization, proportion of patients with no exacerbations, median daily maintenance oral corticosteroids (mOCSs) dose, proportion of patients discontinuing mOCSs completely, Asthma Control Questionnaire-5 score, FEV1, and adverse events (AEs). Results: After 2 years’ follow-up, 73% of patients (599 of 822) had no record of mepolizumab discontinuation. During the 2-year follow-up vs premepolizumab period (N = 822), rates of CSEs, exacerbations requiring ED visit/hospitalization, or hospitalization only were reduced by 74%, 79%, and 73%, respectively (odds ratio for no CSEs, 10.0; 95% CI, 7.55- 13.25). Median daily mOCS dose decreased from 10.0 (quartile 1, 5.0; quartile 3, 14.7) mg at week 0 (n = 297) to 0.0 (quartile 1, 0.0; quartile 3, 5.0) mg at weeks 101 to 104 (n = 168), and the proportion of patients discontinuing mOCS increased progressively to 43% at 1 year and 57% at 2 years. There was a 1.53-point reduction in Asthma Control Questionnaire-5 scores from baseline at 2 years. At months 21 to 24, least square mean FEV1 improved by 142 mL from baseline. Ninety (11%) and 7 (< 1%) patients experienced mepolizumab-related AEs and serious AEs during the follow-up period, respectively. Interpretation: In patients with severe asthma, real-world mepolizumab treatment for 2 years was well tolerated and was associated with sustained reductions in exacerbations and progressive reductions in mOCS use.